Beyond the Political Economy of Electricity and Gas Trade in the Middle East and North Africa Region - World Bank (World Bank, Washington, DC, 2021)
This note is intended to support ongoing efforts to promote Pan-Arab energy trade by highlighting the role and benefits of intra-regional electricity and gas exchange, with a view to improving energy security in the Middle East and North Africa (MENA) region. After some background, this note contributes to discussions on energy security within the region by highlighting various aspects of the current political economy of the energy sector, specifically electricity and gas, which are relevant to the discussion on cooperation for regional integration and their convergence with sustainable development. This note argues that, given the benefits of trade and technological developments outlined herein, the time is right to move from cooperation agreements towards the operationalization and implementation of trade by developing the necessary institutional and regulatory building blocks. Innovative technologies and wider economic trends are converging in new ways that amplify synergies within traditional energy sectors (such as oil, gas, and power) and foster emerging sectors such as hydrogen. Subsequent sections will review the state of electricity and gas trade in the region; sub-regional initiatives to promote interconnections and market integration; and prospects for these sectors. However, some general observations can be drawn in advance about the regional context for overall trade.